(untitled) (Annals of Medical Research, 2021)
Aim: The purpose of this study is to investigate the changes in renal function of the patients having primary hyperparathyroidism with GFR 60 ml/min/1.73 m2 and GFR>60 ml/ min/1.73 m2 before and after PTX. A. Prolonged hypercalcemia leads to impaired renal function and the associated glomerular filtration rate (GFR) decrease. One of the indications of surgery in primary hyperparathyroidism is decreased renal function (GFR 60 ml/min). Discussions about the effect of parathyroidectomy (PTX) on renal function still continue.Materials and Methods: The archive files of 59 patients diagnosed with primary hyperparathyroidism (PHPT), to whom PTX have been performed between January 2008 and October 2019 at Cumhuriyet University Surgical Oncology Clinic, were reviewed retrospectively. GFR was calculated using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation. Patients were divided into two groups according to their GFR values, as GFR60 ml/min/1.73 m2 and GFR>60 ml/min/1.73 m2. Laboratory outcomes of the patients one week before and after PTX were compared. The data of the study were analyzed in SPSS (ver. 23.0) program.Results: Regarding the patients to whom PTX have been performed, 12 patients (20.3%) were male and 47 (79.7%) were female. The mean age was 54.7 years. In patients with GFR60 ml/min/1.73 m2, pre-op mean Parathormone (PTH) value was 1227.36 pg/ml, Calcium (Ca) 10.60 mg/dl, Creatine (Cr) 5.12 mg/dl: while mean PTH value in post-op period was found to be 131.69 (SS: 2.99), Ca: 8.29, Cr: 3.57. In the patient group with GFR>60 ml/min/1.73 m2, pre-op mean PTH was 309.34, Ca: 11.05, Cr: 0.73 (SD: 0.15); whereas post-op PTH was 48.51, Ca: 8.88, Cr: 0.68. In addition, GFR increased in patients in both groups and statistically significant results were obtained between pre and post PTX values.Conclusion: In this study, an improvement was observed after PTX in the renal function of the patients with impaired renal function, whereas GFR values of the patients with normal renal function were increased.